Learning from Mother Nature: Innovative Tools to Boost Endogenous Repair of Critical or Difficult-to-Heal Large Tissue Defects - Cancedda, Ranieri; Bollini, Sveva; Descalzi, Fiorella; Mastrogiacomo, Maddalena; Tasso, Roberta (Frontiers in Bioengineering and Biotechnology, 2017)
For repair of chronic or difficult to heal tissue lesions and defects, major constraints exist to a broad application of cell therapy and tissue engineering approaches, i.e. transplantation of “ex vivo” expanded autologous stem/progenitor cells, alone or associated to carrier biomaterials. To enable a large number of patients to benefit, new strategies should be considered. One of the main goals of contemporary Regenerative Medicine is to develop new regenerative therapies, inspired from Mother Nature. In all injured tissues, when platelets are activated by tissue contact, their released factors promote innate immune cell migration to the wound site. Platelet derived factors, and factors secreted by migrating immune cells create an inflammatory microenvironment, in turn, causing the activation of angiogenesis and vasculogenesis processes. Eventually, repair or regeneration of the injured tissue occurs via paracrine signals activating, mobilizing or recruiting to the wound site cells with healing potential, such as stem cells, progenitors or undifferentiated cells derived from the reprogramming of tissue differentiated cells. This review, largely based on our studies, discusses the identification of new tools, inspired by cellular and molecular mechanisms overseeing physiological tissue healing, that could reactivate dormant endogenous regeneration mechanisms lost during evolution and ontogenesis.